Revisiting imidazolium receptors for the recognition of anions: highlighted research during 2010–2019. (11th November 2020) - Hu, Ying; Long, Shuangshuang; Fu, Haiyan; She, Yuanbin; Xu, Zhaochao; Yoon, Juyoung
Abstract : Research developments of imidazolium receptors for anions (such as DNA, RNA, ATP, etc. ) during 2010–2019 are comprehensively discussed. Abstract : Imidazolium based receptors selectively recognize anions, and have received more and more attention. In 2006 and 2010, we reviewed the mechanism and progress of imidazolium salt recognition of anions, respectively. In the past ten years, new developments have emerged in this area, including some new imidazolium motifs and the identification of a wider variety of biological anions. In this review, we discuss the progress of imidazolium receptors for the recognition of anions in the period of 2010–2019 and highlight the trends in this area. We first classify receptors based on motifs, including some newly emerging receptors, as well as new advances in existing receptor types at this stage. Then we discuss separately according to the types of anions, including ATP, GTP, DNA and RNA.